914 Hydrofluoric acid – effects of skin decontamination on the bioavailability of fluoride. (24th April 2018) - Dennerlein, Kathrin; Hahn, Theresa; Göen, Thomas; Drexler, Hans; Kilo, Sonja
Abstract : Introduction: After dermal contact to occupational hazardous substances the cleaning of exposed skin areas is an important first aid measure to reduce adverse health effects. Due to possible severe systemic intoxication following dermal exposure to hydrofluoric acid (HF) the decontamination of skin should focus on the inactivation of free fluoride ions. The present ex-vivo study investigated the effects of exposure duration and different antidotes on the potential systemic uptake of fluoride. Methods: The transdermal penetration of HF (c=30%) through excised human skin was investigated by using static diffusion cells. After dermal application of the acid (100 µl/0.64 cm 2 ) for 1 min the excess was removed using one dry cotton swab. Subsequently, the skin was cleaned with water, calcium gluconate (CaGl), polyethylene glycol (PEG) 400 or hexafluorine © using a standardised protocol. In a further study, the application time was extended to 3 min to assess the effect of exposure duration. Chemical analyses of fluoride were carried out by GC-MS or via a fluoride-sensitive electrode. Result: Extension of the exposure time from 1 to 3 min led to an enhancement in the transdermal penetration of fluoride, however with similar penetration kinetics. At the end of experiments (6 hour) a 7–fold higher fluoride amount was detected in the receptor fluid (16 vs 114 µg). In all test series maximum flux was achieved within the first hour past exposure. Decontamination of the skin reduced the cumulative penetrated amount of fluoride by 28% (PEG 400), 49% (water) and 64% (CaGl/hexafluorine © ) compared to control. Discussion: The results indicate that the systemic uptake of fluoride ions and therefore possible systemic intoxication after exposure to hydrofluoric acid can be diminished by shortening the exposure duration. Reduction was further increased by decontamination of skin – most by substances which are known to supply the complexation of fluoride ions.